La petite histoire du moulin à eau de la rivière Saint-Pierre et de ses meuniers - Charlebois, Paul-Yvon (Les cahiers d'histoire de Pointe-Saint-Charles, 2009)
Keywords: Communautés religieuses; Côtes; Meunerie; Sulpiciens

"Nous ne voulons pas que nos héritiers soient à la merci des tiens": famille, patrimoine et entreprise chez les Rolland, 1880-1980 - Nootens, Thierry (Revue d'histoire de l'Amérique française, 2007)
Keywords: Famille; Patrimoine

Les industries à LaSalle de 1912 à 2002 - Zaïd, Omar; Zitouni, Khadoudja (Société historique Cavelier-de-LaSalle, 2004)
Keywords: LaSalle

Histoire de la raffinerie de Petro-Canada à Montréal, 1955-2005 - Roy, Michel (Petro-Canada, 2005)
Keywords: Pétrole

De couturière à Soeur Grise. Le parcours inhabituel de Marie Catherine Demers Dessermon dans le Montréal du XVIIIe siècle - Gousse, Suzanne (Cahiers d'histoire, 2009)
Keywords: Communautés religieuses; Confection; Soeurs Grises

Daly et Morin, à la recherche du patrimoine industriel de Lachine - Avon, Hélène (Université de Sherbrooke, 2003)
Keywords: Lachine; Patrimoine

Étude de cas. Abraham de Sola, éditeur juif dans le Montréal victorien - Menkins, Richard (Histoire du livre et de l'imprimé au Canada, vol. II (1840-1918), 2005)
Keywords: De Sola, Abraham; Juifs

Étude de cas. La formation des imprimeurs: L'École des arts graphiques de Montréal. - Leroux, Eric (Histoire du livre et de l'imprimé au Canada, vol. III (1918-1980), 2007)
Keywords: Imprimerie; École des arts graphiques

Les églises: lieux de culte et de culture - Vanlaethem, France (Montréal, la ville aux cent clochers. Regards des Montréalais sur leurs lieux de culte, 2002)
Keywords: Arts sacrés; Patrimoine; Sculpture; Vêtements; Églises

La culture urbaine au Canada et les formes de la culture de l'imprimé aux XVIII et XIX siècles - Lamonde, Yvan (Urban History Review / Revue d'histoire urbaine, 2004)
Keywords: Imprimerie; Librairie; Édition

Les manuels scolaires en Nouvelle-France dans la « Province du Québec » et au Bas-Canada - Aubin, Paul (Histoire du livre et de l'imprimé au Canada, vol. I (des débuts à 1840), 2004)
Keywords: Collège de Montréal; Congrégation de Notre-Dame; Frères Charon; Imprimerie

Le Québec à l'heure de la Révolution américaine - Boyer, Jean-Pierre (1776: Naissance de l'imprimerie et de la liberté d'expression à Montréal, 2008)
Keywords: Du Calvet, Pierre; Gazette Littéraire de Montréal; Idéologies; Imprimerie; Jautard, Valentin; Journalistes; Librairie; Mesplet, Fleury

1776: Naissance de l'imprimerie et de la liberté d'expression à Montréal - Ruelland, Jacques G. (Petit musée de l'impression et Centre d'histoire de Montréal, 2008)
Keywords: Du Calvet, Pierre; Gazette Littéraire de Montréal; Idéologies; Imprimerie; Jautard, Valentin; Journalistes; Librairie; Mesplet, Fleury; Montreal Gazette

Premier imprimeur-libraire à Montréal: Fleury Mesplet (1734-1794), un défenseur des droits humains - de Lagrave, Jean-Paul (1776: Naissance de l'imprimerie et de la liberté d'expression à Montréal, 2008)
Keywords: Gazette Littéraire de Montréal; Idéologies; Imprimerie; Librairie; Mesplet, Fleury; Montreal Gazette

Fleury Mesplet: le pouvoir de la Presse - de Lagrave, Jean-Paul; Ruelland, Jacques G. (1776: Naissance de l'imprimerie et de la liberté d'expression à Montréal, 2008)
Keywords: Gazette Littéraire de Montréal; Idéologies; Imprimerie; Librairie; Mesplet, Fleury; Montreal Gazette

L'Académie de Montréal - de Lagrave, Jean-Paul (1776: Naissance de l'imprimerie et de la liberté d'expression à Montréal, 2008)
Keywords: Gazette Littéraire de Montréal; Idéologies; Imprimerie; Jautard, Valentin; Mesplet, Fleury

Le développement de la presse depuis la Conquête jusqu'à l'Union - Doyon, Nova (1811: De Québec à Montréal, essor de la presse et affirmation d'une parole publique francophone, 2009)
Keywords: Duvernay, Ludger; Imprimerie; Minerve (La); Montreal Gazette; Montreal Herald

1811: De Québec à Montréal, essor de la presse et affirmation d'une parole publique francophone - Doyon, Nova (Petit musée de l'impression et Centre d'histoire de Montréal, 2009)
Keywords: Duvernay, Ludger; Imprimerie; Journalistes; Loyalistes; Minerve (La); Montreal Gazette; Montreal Herald

Ludger Duvernay, le journal La Minerve et la construction identitaire canadienne - Monière, Denis (1811: De Québec à Montréal, essor de la presse et affirmation d'une parole publique francophone, 2009)
Keywords: Duvernay, Ludger; Imprimerie; Journalistes; Minerve (La); Rébellions; Société Saint-Jean-Baptiste

La ville, agent catalyseur de développement: le rôle des municipalités dans l’évolution de l’industrie canadienne des véhicules d’incendie, 1945-1965 - Beauvais, Suzanne (Material History Review / Revue d’histoire de la culture matérielle, 2001)
Keywords: Incendies; Pompiers

Making and Breaking Bread in Jewish Montreal, 1920-1940 - Lerner, Eve (Université Concordia, 2002)
Keywords: Alimentation; Boulangerie; Juifs

La librairie Rolland, 1842-1888 - Déry, Boris (Université du Québec à Montréal, 2003)
Keywords: Librairie

Brasseurs, brasseries et activités brassicoles dans la plaine de Montréal, 1788-1852 - Morin, Stéphane (Université du Québec à Montréal, 2000)
Keywords: Brasserie

Tanneurs et tanneries dans le gouvernement de Montréal au XVIIIe siècle - Perrier, Jocelyne (Université de Montréal, 2002)
Keywords: Artisans; Tannerie

"Le Canada est un païs de bois": Forest Resources and Shipbuilding in New France, 1660-1760 - Delaney, Monique (Université McGill, 2003)
The colonial contribution to the French naval shipbuilding industry in the seventeenth and eighteenth centuries, explored within the context of the forest from which the resources for the industry were taken, was a remarkably successful venture that came to an end with the onset of war. In the past, the end of the French naval shipbuilding industry in New France has been attributed to the action or inaction of France that resulted in the inefficient use of forest resources. Issues of interest in, organization or support of colonial efforts by France, however, were nevertheless, limited by the immutable realities of the colonial forest environment. This thesis argues that the success of the industry, considered within the appropriate context, is a consequence of colonial persistence in the face of constraints imposed by the colonial forest environment---despite these other significant issues. The official correspondence, written by colonial officials in New France, record colonial efforts to supply France with timber and detail the development of a naval shipbuilding industry in the colony. These documents provide source material for a case study that demonstrates the constraints imposed by the colonial forests on the experience of colonists, timber suppliers and shipbuilders. The colonial forest was not the same as the forests in France. A simple transfer of knowledge and practice from one forest to another was insufficient to deal with the differences in climate, forest age, tree species and the extent to which human activity affected the different forests. These differences challenged the way in which colonists could use forest resources for their own needs, for export to France and for naval construction. To consider this use of resources, without considering the differences between the available materials in the colony and those available in France, is to look at the story removed from the setting in which it took place. The unique forest in the colony was the setting in which colonial shipbuilding took place. Any study of the development of this industry, or any other industry that relied on forest resources, must give consideration to the constraints and realities of that forest.
Keywords: Construction navale

Artisans et industries en milieu rural au Québec avant 1851. L’exemple de l’Île Jésus - Logette, Jérôme (Université du Québec à Montréal, 2006)
Keywords: Artisans; Île Jésus

Institutions commerciales de Verdun. D'hier à aujourd'hui (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2006)
Keywords: Commerce de détail; Confection; Magasins; Quartiers; Quincaillerie; Verdun; Vêtements; Épicerie

La formation professionnelle des ouvriers des métiers du livre au Québec au XXe siècle - Leroux, Éric (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2005)
Keywords: Imprimerie; École des arts graphiques; École technique

L'essor du livre illustré au Québec en relation avec les milieux artistiques et éditoriaux français: 1880-1940 - Danaux, Stéphanie (Université de Montréal et Université de Poitiers, 2007)
Keywords: Édition

L’industrie et l’espace urbain. Étude de l’évolution physique du site de la compagnie Dominion Glass, avenue De Lorimier, à Montréal, 1878-1947 - Lampron, Amélie (Université du Québec à Montréal, 2009)
Keywords: Dominion Glass Company

Résidence et liens de parenté des artisans de Montréal en 1741 - Groulx, François; Gauthier, Jean-Richard (Scientia Canadensis: Canadian Journal of the History of Science, Technology and Medicine / Scientia Canadensis : revue canadienne d'histoire des sciences, des techniques et de la médecine, 2000)
Keywords: Artisans; Arts sacrés; Famille